What’s in my fuel tank? Insights into beliefs and preferences for e-fuels and biofuels - Anika Linzenich; Dominik Bongartz; Katrin Arning; Martina Ziefle (Energy, Sustainability and Society, 2023)
Abstract Background Alternative fuels made from biomass or CO2 and water using renewable energy can reduce CO2 and pollutant emissions compared to fossil-based mobility and thus support a transition to a more sustainable transport. The adoption of alternative fuels in transport will ultimately depend on public acceptance and drivers’ willingness to use them. Little is known if and under which circumstances people would accept alternative fuels and which narratives and cognitive beliefs might underlie these usage intentions. Moreover, it is unclear if and how laypeople distinguish between different alternative fuel types in their perceptions, e.g., between fuels made from biomass (biofuels) and fuels produced using electricity (e-fuels). To address the research gap, this study empirically investigated laypeople’s beliefs and expectations towards alternative fuels and preferences for different fuel types. Understanding preferences for fuel types could help in steering public information, support managerial decisions and communication pathways, and promote the roll-out process of fuel innovations. Results Laypeople expected alternative fuels to be made using renewable feedstocks and to not contain gasoline or diesel. Whereas alternative fuels were believed to have advantages concerning environmental and toxic effects and safety compared to diesel and gasoline, they were associated with practical disadvantages for drivers. It was shown that although e-fuels and biofuels both fall under the definition of ”alternative fuels”, laypeople distinguish between them in evaluations of safety, costs, and resource competitiveness: E-fuels were preferred over biofuels and believed to have a lower competition for resources than biofuels. They were also evaluated to be more expensive and comparably less safe to use. Moreover, different adopter groups were identified for both fuels. Conclusions The study has highlighted both adoption drivers and barriers for alternative fuels: Reduced environmental impact could be an important positive factor. In contrast, drawbacks feared by laypeople regarding a low range and an expensive fuel price could be barriers for alternative fuel adoption because they reflect current technical challenges for these fuels. Thus, a more cost-efficient production and higher fuel efficiency should be considered in an acceptance-optimized alternative fuel production.